Über Grenzverteilung eines Funktionals von unabhängigen Zufallsgrößen - Survila, P. (Lithuanian Mathematical Journal, 1971)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: П. Сурвила. О предельном распределении одного функционала от последовательности независимых случайных величин P. Survila. Apie nepriklausomų atsitiktinių dydžių vieno funkcionalo ribinį pasiskirstymą